Glucose-dependent insulinotropic polypeptide stimulates post-absorptive lipid secretion in the intestine - Wang, Rong; Khan, Muhammad Saad Abdullah; Mukherjee, Kundanika; Ghanem, Murooj; Xiao, Changting (Frontiers in Physiology, 2025)
It is increasingly recognized that the intestine can retain a portion of dietary fats for secretion during the post-absorptive state, which has strong implications in metabolic diseases. The regulatory mechanisms of gut lipid storage and release are not well defined. Previous studies showed that the intestine releases locally stored fats in response to several stimulatory cues, such as glucose delivered into the intestinal lumen. It remains unknown how the intestine responds to nutrient signals in this phenomenon. Here we tested the effects of intravenous glucose delivery on intestinal lipid output during the post-absorptive state in mesenteric lymph duct cannulated rats. Compared with intraduodenal glucose delivery, intravenous glucose did not stimulate intestinal lipid output. Intraduodenal glucose was also associated with increases in blood levels of metabolic hormones, among which glucose-dependent insulinotropic peptide (GIP) levels were significantly higher at timepoints corresponding to increased lipid output than in intravenous glucose. Intraperitoneal GIP administration per se robustly stimulated intestinal lipid output. These results support a mechanism that involves glucose sensing at the apical side of the enterocytes and GIP as a potent stimulus for the release of lipid storage from the intestine.